Teachers communication behavior and student achievement in high school biology - Uy, Rhodora B. (2005)
This research aimed to determine students' preferred and perceived biology teacher communication behavior according to cultural group, gender, and type of class. It required a non-experimental research utilizing the survey research method. Three instruments were developed and administered to 314 second year students from four secondary schools in Bayumbong, Nueva Vizcaya. The study revealed that students' preference and perception of biology teacher communication behavior differ significantly. Generally, students prefer a biology teacher who highly shows or exhibits encouragement and appreciation, concern, has a pleasing appearance, friendliness, vitality, and control. Low achievement test scores of the students prove that high agreement between student perception and preference of teachers promote higher achievement to students.